2002
DOI: 10.1006/viro.2001.1239
|View full text |Cite
|
Sign up to set email alerts
|

Hypermodification and Immune Escape of an Internally Deleted Middle-Envelope (M) Protein of Frequent and Predominant Hepatitis B Virus Variants

Abstract: Naturally occurring deletions within the human hepatitis B virus (HBV) preS2 region have frequently been identified in patients with hepatocellular carcinoma (HCC), while chronic carriers without cirrhosis and HCC contain no detectable preS2 deletion variants. We have characterized two different preS2 internal deletion variants from two patients. In addition to several weak phenotypes, our study revealed three unexpected strong phenotypes: (1) a paradoxical "hypermodification" phenomenon was observed with sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 72 publications
5
79
3
Order By: Relevance
“…Recently, two pre-S2 deletion variants of genotype C have been identified in human hepatocellular carcinoma patients, which showed a reduced HBsAg secretion. The secreted portion of HBsAg contained a larger 'hypermodified' M protein (Tai et al, 2002), the nature of which is most likely extensive O-glycosylation, whereas the intracellular M protein had the expected size of the polypeptide without O-gylcosylation (P.-C. Tai, P. K. Chua, W. H. Gerlich and C. Shih, unpublished). In their studies on M protein (genotype D), Werr & Prange (1998) also found expression in COS cells, the secreted portion of the protein to be Oglycosylated, whereas the intracellular portion was smaller and not O-gylcosylated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two pre-S2 deletion variants of genotype C have been identified in human hepatocellular carcinoma patients, which showed a reduced HBsAg secretion. The secreted portion of HBsAg contained a larger 'hypermodified' M protein (Tai et al, 2002), the nature of which is most likely extensive O-glycosylation, whereas the intracellular M protein had the expected size of the polypeptide without O-gylcosylation (P.-C. Tai, P. K. Chua, W. H. Gerlich and C. Shih, unpublished). In their studies on M protein (genotype D), Werr & Prange (1998) also found expression in COS cells, the secreted portion of the protein to be Oglycosylated, whereas the intracellular portion was smaller and not O-gylcosylated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Thr-37 of this protein is, in part, O-glycosylated by a Neu5Ac(a2-3)Gal(b1-3)GalNAca (sialyl-T-antigen), Gal(b1-3)GalNAca (Thomsen-Friedenreich antigen, T-antigen) or GalNAca residue (T n -antigen) (Schmitt et al, 1999). O-glycosylation is more extensive in WHV M surface protein (Tolle et al, 1998) and in HBsAg particles secreted from non-hepatic cells (Werr & Prange, 1998) or in particles carrying certain pre-S2 deletions (Tai et al, 2002). The exact structures of these O-glycans are not known.…”
Section: The L But Not M Protein Mediates Binding To Humanmentioning
confidence: 99%
“…The deletion site of this protein defines a cytotoxic T-lymphocyte epitope, and ⌬S2-LHBs may represent an immune escape mutant. [8][9][10] These pre-S2 mutants are becoming increasingly prevalent in serum and liver tissues of patients with chronic HBV infection and HCC. [8][9][10] ⌬S2-LHBs is localized in the endoplasmic reticulum (ER) and has been implicated in the induction of ER stress responses.…”
Section: H Epatitis B Virus (Hbv) Is Regarded As An Etiological Factomentioning
confidence: 99%
“…[8][9][10] These pre-S2 mutants are becoming increasingly prevalent in serum and liver tissues of patients with chronic HBV infection and HCC. [8][9][10] ⌬S2-LHBs is localized in the endoplasmic reticulum (ER) and has been implicated in the induction of ER stress responses. 11 Interestingly, hepatocytes containing these mutants usually form clusters and undergo clonal proliferation, 12 consistent with the suggestion that ⌬S2-LHBs may confer a growth advantage on hepatocytes and play a role in HBV-related hepatocarcinogenesis.…”
Section: H Epatitis B Virus (Hbv) Is Regarded As An Etiological Factomentioning
confidence: 99%
“…40 Pre-S2/S mutants that overaccumulate envelope polypeptides within the cell have also been observed in association with advancing liver disease and may be partially responsible for ground-glass hepatocytes and perhaps even HCC lesions. 41 In addition, the overexpression of LHBs protein in transgenic mice has been shown to be cytopathic, possibly leading to liver injury, regenerative hyperplasia, chronic inflammation, oxidative DNA damage, hepatocyte aneuploidy, and eventually progression to HCC. 42 HBSP is encoded by one of the spliced RNAs of HBV, 43 and its expression induces apoptosis without cell-cycle block.…”
Section: Integration Of Hbv Dnamentioning
confidence: 99%